I thought this question looked familiar.
Did it on Friday
http://www.jiskha.com/display.cgi?id=1455295033
Can anyone show me how to simplify this step-by-step? THANKS A MILLION!
(6x^-2)^2(0.5x)^4
3 answers
x ^ - 2 = 1 / x ^ 2
( 6 x ^ - 2 ) ^ 2 =
( 6 / x ^ 2 ) ^ 2 =
6 ^ 2 / ( x ^ 2 ) ^ 2 =
36 / x ^ 4
( 0.5 x ) ^ 4 =
0.5 ^ 4 * x ^ 4 =
0.0625 x ^ 4
( 6 x ^ - 2 ) ^ 2 0.5 x ^ 4 =
( 36 / x ^ 4 ) * 0.0625 x ^ 4 =
36 * 0.0625 * x ^ 4 / x ^ 4 =
36 * 0.0625 = 2.25
( 6 x ^ - 2 ) ^ 2 =
( 6 / x ^ 2 ) ^ 2 =
6 ^ 2 / ( x ^ 2 ) ^ 2 =
36 / x ^ 4
( 0.5 x ) ^ 4 =
0.5 ^ 4 * x ^ 4 =
0.0625 x ^ 4
( 6 x ^ - 2 ) ^ 2 0.5 x ^ 4 =
( 36 / x ^ 4 ) * 0.0625 x ^ 4 =
36 * 0.0625 * x ^ 4 / x ^ 4 =
36 * 0.0625 = 2.25
Thanks guys! I owe you one!